Penggunaan Economic Value Added Sebagai Kriteria dalam Penerapan Creating Shared Value - Elfina Astrella Sambuaga (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2020)
This study aims to analyze the values ​​of Creating Shared Value that exist in companies that have Economic Value values, as well as understand the role of the application of Creating Shared Value as a corporate strategy and identify the impact of the application of Creating Shared Value for the company. The population in this study amounted to 213 companies engaged in the agriculture, mining and manufacturing sectors which are not included in other industrial subsectors. The analytical method used in this study includes the calculation of Economic Value Added aims to determine the existence of economic added value obtained by the company through its activities, then analyze the existence of the value of Creating Shared Value by identifying the activities carried out by the company in accordance with the guidelines for creating Shared Value. Based on the results obtained, there is a positive correlation between the application of Creating Shared Value and the value of Economic Value Added. This is evidenced by companies that have positive Economic Value Added, ​​that tend to apply Creating Shared Value as a form of corporate strategy.